Exploring the Intersection of National Innovation Systems and the Transformative Impact of Digitization - ECHEFAJ , Fatima Ezzahra (Revue Internationale du Chercheur, 2023)
This article delves into the intricate and dynamic interplay between the national innovation system (NIS) and the transformative influence of digitization, a phenomenon that is fundamentally reshaping economies and societies on a global scale. In the face of this digital revolution, it becomes increasingly imperative to comprehend not only how the traditional structures of NIS can adapt to the demands of digitization but also how they can effectively harness the unprecedented opportunities it presents. With a comprehensive approach, this article delves into the complexities of integrating digitization into NIS. It critically analyzes the challenges that arise from this fusion, including issues related to workforce skills, regulatory frameworks, ethical considerations, and the digital divide. In addition to its analysis, the article provides valuable policy implications and actionable recommendations. These insights are aimed at policymakers, researchers. By shedding light on this complex interplay, the article underscores the need for a strategic and forward-thinking approach to aligning NIS with the rapidly evolving landscape of digitization. It emphasizes the importance of cultivating an inclusive and collaborative environment that encourages innovation, fosters digital skills, and leverages technology for sustainable economic development. In conclusion, this article offers a roadmap for harnessing the power of digitization within NIS, shaping a future where innovation thrives amidst the digital revolution.